The effect of transformational management in the organization on quality of work life of the staff of Shohada-ye Tajrish Hospital in Tehran - Seyed Mohammad Hasan Safi; Mohammad Hossein sadeghian (Tehran University of Medical Sciences, 2021)
Background:The most important and difficult process in any organization is to create change in the organization because today organizations have to react to changes in the environment.The purpose of this study was to investigate the effect of transformational management on quality of work life of the staff of Shohada-ye Tajrish Hospital in Tehran. Materials & Methods:The is a descriptive-analytic and cross-sectional study that was conducted in Shohada-ye Tajrish Hospital in Tehran in 2020. Data collection tools were Transformational Management Questionnaire(Bass and Olivier)and Quality of Work Life Questionnaire(Walton 1973). Based on Cochran's formula, 234 employees of Shohada-ye Tajrish Hospital in Tehran were selected as study population.The reliability and validity of the measuring tools were evaluated using Cronbach's alpha coefficient and confirmatory factor analysis. Pearson correlation test and structural equation test were used to analyze the data. Results:The research findings indicated that there was a positive and significant correlation between transformational management with safe and healthy work environment, growth opportunity and security, fair and adequate pay, employee legalism,social affiliation,social cohesion and integration, development of human capabilities and the general atmosphere of working life. In addition, 92% of the variance in quality of work life was explained by the research model. Conclusion:Considering the impact of transformational management on the development of human capabilities, senior managers should formulate and implement appropriate programs to improve the quality of work life and provide conditions for employees to enjoy their organization and work.